Synbiotic Effects of Enzyme and Probiotics on Intestinal Health and Growth of Newly Weaned Pigs Challenged With Enterotoxigenic F18+Escherichia coli - Duarte, Marcos Elias; Tyus, James; Kim, Sung Woo (Frontiers in Veterinary Science, 2020)
This study was aimed to investigate the effect of dietary supplementation with xylanase and probiotic on growth performance, and intestinal health of nursery pigs challenged with enterotoxigenic Escherichia coli (ETEC). Sixty-four newly weaned pigs (32 barrows and 32 gilts with 7.9 ± 0.4 kg BW) were allotted in a randomized complete block design (2 x 2 factorial). Two factors were ETEC challenge (oral inoculation of saline solution or E. coli F18+ at 6 x 109 CFU) and synbiotic (none or a combination of xylanase 10,000 XU/kg and Bacillus sp. 2 x 108 CFU/kg). All pigs were fed experimental diets following NRC (2012) in 2 phases (P1 for 10 d and P2 for 11 d). The ETEC was orally inoculated on d 7 after weaning. Feed intake and BW were measured on d 7, 10, 15, and 20. On d 20, pigs were euthanized to collect samples to measure gut health parameters and microbiome. Synbiotic increased (P < 0.05) ADG in phase 1 and ETEC reduced (P < 0.05) ADG and G:F in the post-challenge period. ETEC increased (P < 0.05) the fecal score of pigs from d 7 to 13, however synbiotic reduced (P < 0.05) it at d 9 and 11 in challenged pigs. ETEC increased (P < 0.05) mucosal MDA, IL-6, Ki-67+, and crypt depth, whereas synbiotic tended to reduce TNFα (P = 0.093), protein carbonyl (P = 0.065), and IL-6 (P = 0.064); reduced (P < 0.05) crypt depth and Ki-67+; and increased (P < 0.05) villus height. ETEC reduced (P < 0.05) the relative abundance of Bacteroidetes and Firmicutes and increased (P < 0.05) the relative abundance of Proteobacteria. In conclusions, ETEC challenge reduced growth performance by affecting microbiome, immune response, and oxidative stress in the jejunum. Synbiotic enhanced growth performance by reducing diarrhea, immune response, and oxidative stress in the jejunum.